An Unusual Drug Reaction To Carbamazepine - Chakravarty K; Chanda M (Wolters Kluwer Medknow Publications, 1995)
Cases of two patients who developed psoriasiform lesions following carbamazepine (CBZ) therapy are reported here for its rarity.